Uncertainty components estimation by calibration of scanning electron nanoscopes - Шантир, Антон Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
Nowadays, hundreds of companies in different countries conduct the researches in the field of the nanotechnology, use or create nanoproducts. The important task of the nanotechnologies, particularly in the field of the nanoelectronics, is the development of the integrated circuits with the nanometer technological sizes and products based on the nanoelectronic components, whose quality depends on the accuracy of measurement of the characteristics of elements, whose sizes correspond to limiting technological capabilities. The model of the measuring signal of the scanning electron nanoscope was suggested. The uncertainty of the samples, which were studied in the nanoscopes, were estimated and the change of their characteristics during the measurement was described. The main sources of uncertainty were analyzed by the calibration of the scanning electron nanoscopes in the nanometer range of the measurement. The possible ways to improve the accuracy of the calibration using standard samples with known sizes of the structural elements were shown by the introduction of the appropriate processing of the measuring signal. The possibilities of construction of alternative standard samples were shown. The results can be used to develop new methods of the calibration of the scanning electron nanoscopes and standard samples of the nanometer range.